2009
DOI: 10.1039/b815598d
|View full text |Cite
|
Sign up to set email alerts
|

Phosphopeptide enrichment on functionalized polymer microspots for MALDI-MS analysis

Abstract: On-plate enrichment of phosphopeptide digests followed by MALDI-MS is attractive for analyzing small quantities of phosphoproteins because it involves minimal sample handling and reduces sample loss. This work describes a method for modification of Si wafers, which serve as MALDI plates, with 250 microm-diameter microspots of phosphopeptide-binding polymer brushes enclosed by a hydrophobic poly(dimethylsiloxane) (PDMS) layer. Formation of the patterned surface occurs by heating a patterned PDMS stamp on a Si w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Dunn, Reid, and Bruening (2010) enumerated several onplate protocols for phosphopeptides; immobilized metal affinity chromatography (IMAC) MALDI plates include: commercial affinity chips (e.g., the so-called ''ProteinChip'' commercialized by Ciphergen Biosystems, Fremont, CA), monolayers of immobilized metal-ion complexes, polymer-modified plates and zirconium phosphonate films; while MALDI plates modified with metal oxides include targets containing zirconium oxide and titanium dioxide. An exciting example of a method for the onplate enrichment of phosphopeptides is the one presented by Wang and Bruening (2009): the authors reported modification of silicon wafers with 250 mm-diameter microspots, which contain phosphopeptide-binding polymer brushes (Fig. 5).…”
Section: A Preconcentration and Sensitivity Enhancementmentioning
confidence: 98%
See 1 more Smart Citation
“…Dunn, Reid, and Bruening (2010) enumerated several onplate protocols for phosphopeptides; immobilized metal affinity chromatography (IMAC) MALDI plates include: commercial affinity chips (e.g., the so-called ''ProteinChip'' commercialized by Ciphergen Biosystems, Fremont, CA), monolayers of immobilized metal-ion complexes, polymer-modified plates and zirconium phosphonate films; while MALDI plates modified with metal oxides include targets containing zirconium oxide and titanium dioxide. An exciting example of a method for the onplate enrichment of phosphopeptides is the one presented by Wang and Bruening (2009): the authors reported modification of silicon wafers with 250 mm-diameter microspots, which contain phosphopeptide-binding polymer brushes (Fig. 5).…”
Section: A Preconcentration and Sensitivity Enhancementmentioning
confidence: 98%
“…The largest number of applications of the affinity-based onplate preconcentration of analytes is seen in the field of phosphoproteomics (e.g., Dunn et al, 2008;Blacken et al, 2009;Torta et al, 2009;Wang & Bruening, 2009). Dunn, Reid, and Bruening (2010) enumerated several onplate protocols for phosphopeptides; immobilized metal affinity chromatography (IMAC) MALDI plates include: commercial affinity chips (e.g., the so-called ''ProteinChip'' commercialized by Ciphergen Biosystems, Fremont, CA), monolayers of immobilized metal-ion complexes, polymer-modified plates and zirconium phosphonate films; while MALDI plates modified with metal oxides include targets containing zirconium oxide and titanium dioxide.…”
Section: A Preconcentration and Sensitivity Enhancementmentioning
confidence: 99%
“…A very low detection limit, a significantly improved phospho-profiling capability, and a simple experimental approach were reported. Wang and Bruening [43] described an interesting method for modification of Silicon wafers, which serve as MALDI plates with 250 μm-diameter microspots of phosphopeptide-binding polymer brushes enclosed by a hydrophobic poly(dimethylsiloxane) layer. Enrichment resulted in a 5-fold decrease in MALDI-MS detection limits and femtomole-level sensitivity.…”
Section: On-plate Enrichment For Maldi-msmentioning
confidence: 99%
“…In order to enrich the phosphopeptides most of the new methods make use of the high affinity of the phosphoryl group to metals and metal oxides (e.g., on immobilized metal affinity chromatography (IMAC) [2][3][4][5] , metal oxide affinity chromatography (MOAC) 1,[6][7][8][9][10][11][12][13][14] , sequential immobilized metal affinity chromatography (SIMAC) 15 and direct on-target enrichment [16][17][18][19][20][21][22][23] ). Mass spectrometry (MS) is then commonly used to analyze the peptides.…”
Section: Introductionmentioning
confidence: 99%